SOURCE RISK ASSESSMENT FOR HEAVY METALS IN SOIL ON THE SITE OF A HYDROCARBON POWER PLANT - RAMONA-CARMEN HĂRȚĂU; CLAUDIU-ȘTEFAN URSACHI; SIMONA PERȚA-CRIȘAN; SIMONA GAVRILAȘ; FLORENTINA-DANIELA MUNTEANU (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
The present study aims to assess the soil quality on a hydrocarbon power plant site in Arad, Romania. It investigates the evolution of heavy metal concentrations (Cu, Zn, Pb, Ni, Cd, and Cr) to establish source-related risks. For this purpose, the Global Pollution Index (GPI) was used, calculated for soil sampling points in the licensed area, and the database of monitored indicators was processed. Sampling was carried out annually between 2011 and 2020. An Individual Pollution Index (IPi) was calculated for each heavy metal and reference value, taking into account the Geochemical Background Level (Bi) specific to Romania. The correlation between these indices and the degree of pollution for each soil sample monitored was carried out to the legal provisions. Heavy metal concentrations (Cs, i) were evaluated in relation to the national legislation for less sensitive land use. Finally, the GPI was determined, and based on these values, the overall soil pollution status was assessed. Based on the determined CFi values and the corresponding Toxicity Factors (Ti) of heavy metals, the environmental impact was assessed by environmental risk analysis using the Risk Indices (ERi and R.I.) method. All the analyzed indicators were within the legal limits during the studied period, except Cd, where the alert threshold was exceeded in 2019 and 2020.